2018
DOI: 10.31486/toj.17.0101
|View full text |Cite
|
Sign up to set email alerts
|

Predicting American Board of Emergency Medicine Qualifying Examination Passage Using United States Medical Licensing Examination Step Scores

Abstract: Background:The objective of the current study was to determine whether emergency medicine residents' United States Medical Licensing Examination (USMLE) scores are significantly associated with first-attempt passage of the American Board of Emergency Medicine (ABEM) qualifying (written) examination. We hypothesized that USMLE Step 2 Clinical Knowledge (CK) scores would be useful in predicting students who passed the ABEM qualifying examination on their first attempt. Methods: For this retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…We received one unpublished manuscript 23 and one in press (now published) manuscript 22 from these queries. In total, we included 15 published articles, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] one unpublished manuscript, 23 and 11 abstracts [24][25][26][27][28][29][30][31][32][33][34] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We received one unpublished manuscript 23 and one in press (now published) manuscript 22 from these queries. In total, we included 15 published articles, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] one unpublished manuscript, 23 and 11 abstracts [24][25][26][27][28][29][30][31][32][33][34] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The authors of these studies defined success by the following: in-training examination (ITE) performance, 13,18,19,25,[27][28][29][30]34 passage of the American Board of Emergency Medicine (ABEM) Qualifying Examination (QE) 11,22,29 or American Osteopathic Board of Emergency Medicine (AOEBM) written examination 14,31 average ACGME core competencybased Likert-scale faculty evaluation scores, 8,10,21,26 or a graduation rank order list (GROL). 12,15,16,19,20,23,27,32,33 A GROL is a ranked list of graduates, as determined by a vote of faculty or program leaders, upon or after graduation, made specifically for the purposes of the study.…”
Section: Resultsmentioning
confidence: 99%
“…While not part of our primary objective, we found that while Grit‐S scores did not correlate with the need for remediation, the need for remediation did predict success on the ITE, which would be expected as many residents undergo remediation for low ITE scores. Additionally, USMLE Step 2 CK (Clinical Knowledge) scores have been shown to predict passage of the ABEM Qualifying Examination on the first attempt . We did not collect data regarding residents’ USMLE scores in this study so it is possible that there may have been a correlation between grit and Step 2 CK scores that was not assessed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The medical education community recognizes that performance on USMLE Step 1 evaluates medical knowledge and predicts performance on other standardized tests, such as in-training and certification examinations. [5][6][7][8][9][10] However, there are few data to suggest that USMLE Step 1 and 2 scores predict performance across other critical competency domains, such as patient care, communication, and professionalism. [11][12][13][14] The Association of American Medical Colleges, American Medical Association, Educational Commission for Foreign Medical Graduates, Federation of State Medical Boards, and National Board of Medical Examiners convened a multistakeholder Invitational Conference on USMLE Scoring (InCUS) in March 2019 to address issues concerning USMLE score reporting, primary and secondary uses, and the transition from undergraduate medical education to graduate medical education (GME).…”
Section: Introductionmentioning
confidence: 99%